Effect of Moringa oleifera Seed Powder on the Clarity, Colloidal Particles, and Nutritional Contents of Cashew Apple Juice - Cajethan U. Ugwuoke; Felicitas G. Ugwuoke; Benedicta A. Omeje; Godwin E. Eze; Nnennaya S. Monwuba; Florence O. Ifeanyieze; Juliana A. Ukonze (Scientifica)
Cashew apple juice is a good source of vitamins, minerals, and other nutrients. Cashew apples are being wasted due to lack of processing and are not much cherished because of its astringency. Some of the available clarifying agents are costly and are mainly imported. The study was, therefore, aimed at finding out the effect of M. oleifera seed powder on the clarity and phytochemical and nutritional contents of cashew apple juice. The study adopted an experimental design where 5 g, 10 g, 15 g, and 20 g of M. oleifera seed powder were used to clarify 250 cm3 of cashew apple juice. The setups were filtered using a filter paper after standing for an hour to get the clarified juice. The clarity of each filtrate was determined using an atomic absorption spectrometer (AAS). Similarly, the tannin, lignin, pectin, protein, starch, calcium, zinc, copper, magnesium, and vitamin C were determined following the procedure of the Association of Official Analytical Chemists (AOAC). Results showed that cashew apple juice clarified with 10 g/250 cm3 gave the best clarity. The colloidal particle contents of cashew apple juice were significantly reduced by the use of M. oleifera seed powder. It was equally found out that the clarified cashew apple juice contained an appreciable amount of nutrients. The flavour, colour, and general acceptability of the clarified cashew apple juice were very much liked by the panellist while the aroma was moderately liked. The study recommended that M. oleifera seed powder should be used for clarifying cashew apple juice and be included at the rate of 10 g/250 cm3.